Makna Puisi “Pulang Kampung” Karya Iqbal Naspa Tinjauan Semiotika Riffaterre - Diana, Jumianti (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to express the meaning of the poem entitled "Pulang Kampung" by Iqbal Naspa using Riffaterre's semiotic approach, namely heuristic and hermeneutic reading. The research method used is descriptive qualitative. Data collection was carried out using library techniques, listening, and taking notes. Data analysis was carried out using the semiotic reading model. The results of the research showed that the poem tells the parents who have several hopes for their children. First, they expect that children who have migrated will still return home to visit their parents back home. Second, they wish that their children realize that they were once in their mother's womb. Finally, they remind their children to have filial obedience and they always pray for this.